Rheological, mechanical and durability evaluation of alkali-activated pastes and concretes designed based on fly ash and steel slag - Araújo, Lucas Benício Rodrigues (2023)
ARAUJO, Lucas Benício Rodrigues. Rheological, mechanical and durability evaluation of alkali-activated pastes and concretes designed based on fly ash and steel slag. 2023. 144f. Dissertação (Mestrado em Engenharia Civil: Estrutura e construção Civil) - Centro de Tecnologia, Univrsidade Federal do Ceará, Fortaleza. 2023.